Analisis Yuridis Pengesahan Jual Beli Tanah Bersertifikat Hak Milik Melalui Putusan Pengadilan - Dewi Budiani Hendrawan (Fakultas Hukum Universitas Islam Malang, 2021)
ABSTRACTThe ratification of the sale and purchase of land with title certificates through a court decision is an attempt to ratify a sale and purchase agreement that is carried out without a PPAT sale and purchase deed. Based on this background, the formulation of the problem raised is how the juridical analysis of the legalization of the sale and purchase of land with title certificates is made through a court decision and what are the legal consequences of the court's decision that authorizes the sale and purchase. This research uses normative juridical law research with a law approach and a case approach. Processing of legal materials obtained in the literature study and document studies were analyzed normatively using systematic grammatical interpretation methods.The result of the research is that the sale and purchase of land with title certificates as long as it fulfills the provisions of Article 1320 of the Civil Code only creates a sale and purchase agreement but does not transfer land rights to the buyer, so that the ratification is carried out through a lawsuit by the buyer or his heirs against the seller in the District Court. According to its nature, the decision in this case is a Condemnatoir decision and has permanent legal force.Key words : Legalization of land sale and purchase, certificate of ownership, court decisionABSTRAKPengesahan jual beli tanah bersertifikat hak milik melalui putusan pengadilan merupakan upaya untuk mengesahkan perjanjian jual beli yang dilakukan tanpa akta jual beli PPAT. Berdasarkan latar belakang tersebut, rumusan masalah yang diangkat adalah bagaimana analisis yuridis pengesahan jual beli tanah bersertifikat hak milik melalui putusan pengadilan dan bagaimana akibat hukum terhadap putusan pengadilan yang mengesahkan jual beli tersebut. Penelitian ini menggunakan penelitian hukum yuridis normatif dengan pendekatan undang-undang dan pendekatan kasus. Pengolahan bahan hukum diperoleh dalam studi kepustakaan dan studi dokumen dianalisa secara normatif menggunakan metode interpretasi gramatikal secara sistematis.Hasil penelitian adalah jual beli tanah bersertifikat hak milik sepanjang memenuhi ketentuan Pasal 1320 KUH Perdata baru menimbulkan perjanjian jual beli namun tidak memindahkan hak atas tanah kepada pembeli, sehingga pengesahannya dilakukan melalui gugatan oleh pihak pembeli atau ahli warisnya terhadap pihak penjual di Pengadilan Negeri.Menurut sifatnya, Putusan dalam kasus ini adalah putusan Condemnatoir dan berkekuatan hukum tetap.Kata Kunci : Pengesahan jual beli tanah, bersertifikat hak milik, putusan pengadilan